Early Film Theories in Italy, 1896-1922 - Mazzei, Luca; Alovisio, Silvio, 1968-; Casetti, Francesco; Project Muse. (Amsterdam : Amsterdam University Press, 2017)
This collection is the first to bring together scholars to explore the ways in which various people and groups in Italian society reacted to the advent of cinema. Looking at the responses of writers, scholars, clergymen, psychologists, philosophers, members of parliament, and more, the pieces collected here from that period show how Italians developed a common language to describe and discuss this invention that quickly exceeded all expectations and transcended existing categories of thought and artistic forms. The result is a close-up picture of a culture in transition, dealing with a 'scandalous' new technology that appeared poised to thoroughly change everyday life.
The Throb of the Cinematograph / Francesco Casetti -- Section 1 -- Cinema and Modern Life / Francesco Casetti -- Cinematography / Edipi -- The Philosophy of Cinematograph / Giovanni Papini -- Summertime Spectacles: The Cinema / Gaio -- Why I Love the Cinema / Maffio Maffii -- The Movie Theatre Audience / Giovanni Fosse -- The Art of Celluloid / Crainquebille -- The Triumph of the Cinema / Ricciotto Canudo -- The Death of the Word / Fausto Maria Martini -- Section 2 -- Film in Transition / Francesco Casetti -- The Museum of the Fleeting Moment / Lucio d'Ambra -- The Woman and the Cinema / Haydee -- Darkness and Intelligence / Emanuele Toddi -- A Spectatrix is Speaking to You / Matilde Serao -- Motion Pictures in Provincial Towns / Emilio Scaglione -- Cinematic Psychology / Edoardo Coli -- The Cinematograph Doesn't Exist / Silvio d'Amico -- The Cinema: School of the Will and of Energy / Giovanni Bertinetti -- The Close-up / Alberto Orsi -- The Soul of Titles / Ernesto Quadrone -- Section 3 -- Cinema at War / Luca Mazzei -- The War, from Up Close / Nino Salvaneschi -- That Poor Cinema / Renato Giovannetti -- Families of Soldiers / Luigi Lucatelli -- War for the Profit of Industry / Renato Giovannetti -- The War and Cinematograph / g.pr. -- Max Linder Dies in The War / Lucio d'Ambra -- Cinema of War / Saverio Procida -- Section 4 -- Politics, Morality, Education / Silvio Alovisio -- The Motion Pictures and Education / Domenico Orano -- The Intuitive Method in Religious Education / Romano Costetti -- The Cinema and Its Influence on the Education of the People / Giovanni Battista Avellone -- The Cinematograph in the Schools / Francesco Orestano -- Speech at the People's Theatre / Vittorio Emanuele Orlando -- Cinema for the Cultivation of the Intellect / Angelina Buracci -- Educational Cinema / Ettore Fabietti -- Section 5 -- Film, Body, Mind / Silvio Alovisio -- Collective Psychology / Pasquale Rossi -- About Some Psychological Observations Made During Film Screenings / Mario Ponzo -- Concerning the Effects of Film Viewing on Neurotic Individuals / Giuseppe d'Abundo -- The Ongoing Battle between Gesture and Word / Mariano Luigi Patrizi -- The Cinematograph in the Field of Mental Illness and Criminality: Notes / Giuseppe Vidoni -- Cinema and Juvenile Delinquency / Mario Ponzo -- Section 6 -- The Aesthetic Side / Luca Mazzei -- Problems of Art: Expression and Movement in Sculpture / Corrado Ricci -- Scenic Impressionism / Sebastiano Arturo Luciani -- The Aesthetics of Cinema / Goffredo Bellonci -- The Poetics of Cinema / Sebastiano Arturo Luciani -- Manifesto for a Cinematic Revolution / Goffredo Bellonci -- Theatre and the Cinema / Antonio Gramsci -- The Futurist Cinematography / Remo Chiti -- In the Beginning Was Sex / Antonio Gramsci -- Rectangle-Film (25 x 19) / Emanuele Toddi -- The Proscenium Arch of My Cinema / Anton Giulio Bragaglia -- My Views on the Cinematograph / Lucio d'Ambra -- Meditations in the Dark / Michele Biancale -- Section 7 -- Theory in a Narrative Form / Luca Mazzei -- Colour Film / Roberto Tanfani -- At the Cinema / Luigia Cortesi -- A Phantom Pursued / Alberto Lumbroso -- Miopetti's Duel / Aldo Borelli -- Pamela-Films / Guido Gozzano -- Feature Film / Pio Vanzi -- Me, Riri, and Love in Slippers / Luciano Doria -- A Cinematic Performance / Federigo Tozzi -- Life, a Glass Theatre / Pier Maria Rosso di San Secondo -- The Shears' Reflection / Guido Gozzano.
Undetermined.
Description based on print version record.
Keywords: Motion pictures -- Social aspects; Motion pictures -- Philosophy; Motion pictures and the arts; Motion pictures -- Aesthetics; Motion pictures; Intellectual life; PERFORMING ARTS -- Film & Video -- General; PERFORMING ARTS -- Reference; The arts; Films, cinema; Film, TV and radio; Film theory and criticism; Cinema et arts -- Italie; Cinema -- Aspect social -- Italie; Cinema -- Italie -- Esthetique; Cinema -- Italie -- Philosophie; Cinema -- Italie -- Histoire; Motion pictures and the arts -- Italy; Motion pictures -- Social aspects -- Italy; Motion pictures -- Italy -- Aesthetics; Motion pictures -- Italy -- Philosophy; Motion pictures -- Italy -- History; Italy; Italie -- Vie intellectuelle -- 20e siecle; Italy -- Intellectual life -- 20th century; History; Electronic books